APLIKASI MODEL PEMBELAJARAN STAD DENGAN MEDIA ANIMASI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN KIMIA DASAR MATERI STOIKIOMETRI - Manasikana, Oktaffi Arinna (Discovery, 2017)
Learning is a process of negotiation, the meaning, and the process of assimilation of the new concepts into cognitive schema that is owned by the student. In order that it occurs a problem faced by every individual with respect to the ability to absorb new information. Each individual will have different speeds and produce different achievements also depend on factors that surrounded him. One important factor is the method of teaching. Various methods are available to explain to the students but each method will have different characteristics. In addition to the method, also pay attention to learning media in accordance with the character of the material, the method chosen and the students. In this research method used is a method STAD it is selected so that the quality of learning in the aspect of the interest and activity of increasing student learning. Media animation of the character this adjusting stoichiometry tend to be abstract. From the selection of a suitable model and the media are expected to increase learning achievement so that the quality of learning achieved. Keywords : STAD, Media Animasi